Growth and Inequality in Pakistan. Edited by Keith Griffin and Azizur Rahman Khan. London: Macmillan. 1972. (The Pakistan Development Review, 1974)
This volume is a collection of selected analytical articles bn Pakistan's economy during the 1960s. AH the contributors to this volume having been associated with the Pakistan Institute of Development Economics (PIDE), they are well versed with the economy of Pakistan and their criticisms and judgments carry authority. This volume, thus, is a modest tribute to the PIDE which has established itself as a centre of excellence in solid and unbiased research in applied economics.